ANALISIS DETERMINAN BELANJA DAERAH DI KABUPATEN/KOTA PROVINSI JAWA BARAT DALAM ERA OTONOMI DAN DESENTRALISASI FISKAL - Hadi Sasana (Jurnal Bisnis dan Ekonomi, 2011)
Local autonomy and implementation of fiscal decentralization are expected to improveequality of local developments, in accordance with the motivation of local governments to developtheir region based on their specific potentiality. However, some researches indicate that althoughdecentralization has been implemented in Indonesia for almost a decade, the regions still stronglydepend on the central government financially. This research examine regionally original income,gross regional domestic product, transfer fund, and population, to local government spending inregencies/municipalities in West Java Province. The important findings of this research indicatethat gross regional domestic product, transfer fund, and population positive influence to localgovernment spending in regencies/municipalities in West Java Province.Key Words: regionally original income, gross regional domestic product, transfer fund,population, and local government spending